The neglected issue of sleep: A curricular and home-based intervention for improving sleep patterns among sixth-class children in an Irish urban school with high levels of poverty. Issue 4 (2nd October 2019) - Hargadon, Ciara; Downes, Paul
Abstract : This study seeks to examine the importance of sleep health in an Irish urban school context of high poverty. It adopts an action research approach to conduct small-scale research with a non-probability sample of twenty-four sixth class pupils, to ascertain whether a five-week school and home based intervention can improve; sleep behaviours among the participants; self-reported daytime sleepiness of participants; and self-reported motivation to improve sleep health. The results indicated a notable improvement in child-reported daytime sleepiness, particularly among high-risk children. There was also a reduction in children reporting a bedtime post-midnight after the intervention. This intervention is innovative in its approach, as it provides a possible model for implementing a sleep health programme in the Irish primary curriculum to address the current Irish national policy neglect of this issue. It incorporates a parental involvement element, which has been recommended by previous international sleep interventions [Blunden et al. 2012 . "Does Sleep Education Change Sleep Parameters? Comparing Sleep Education Trials for Middle School Students in Australia and New Zealand." The Open Sleep Journal 5: 12–18]. In addition, it aims to exert behaviour change, not just changing attitudes. These results, coupled with a positive feedback from children, their parents and class teacher, suggest positive potential for curricular multi-disciplinary model interventions in addressing sleep health needs among school-aged children.